Children's Mobilities Interdependent, Imagined, Relational - Murray, Lesley; Cortés-Morales, Susana (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2019)
This book offers a critical and comprehensive analysis of children's mobilities by focusing on its interdependent, imagined and relational aspects. In doing so, it challenges existing literature, which, in mobilities studies, tends to overlook the mobilities of marginalised social groups; in social science more generally, tends to immobilize children's studies; and in children's mobility studies has mainly focused on the 'independent' and corporeal travel of children. The book situates children's mobilities in wider contexts, offering an interdisciplinary and critical perspective throughout and drawing on scholarship at the confluence of childhood and mobilities and a range of research to offer new insights that inform the field of mobilities and studies of childhood. In this way, the book aims at widening the perspective on children's mobility towards the inclusion of diverse age groups and of the manifold forms of mobilities that are part of children's lives, from an interdependent and relational point of view.